KINERJA PENYULUH PERTANIAN DALAM MEMBERDAYAKAN PETANI - Sutrisno, Sutrisno (Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kabupaten Pati, 2016)
ENGLISHPerformance of agricultural extension agent refers to the concepts of empowerment that can improve capacity and the indipendence of farmers. This paper aims to describe the performance of agricultural extension agent in empowering farmers. Performance of agricultural extension agent is perceived by the satisfaction level of farmers who receive services from the agents. Factors that give positive and significant influence to the performance of agricultural extension agent in empowering farmers are: (1) The education of farmers both formal and non-formal educations; (2) The characteristics of the social system (e.g. social values of culture, farmers access to extension services and facilitation of agribusiness by relevant government institutions); and (3) The competence of agricultural extension agent (e.g. competence of extension agent to communicate; competence of extension agent to educate farmers and competence of extension agent in social interaction).Â INDONESIAKinerja penyuluh mengacu kepada konsep-konsep pemberdayaan yang mampu meningkatkan kapasitas dan kemandirian petani. Tulisan ini bertujuan untuk menggambarkan kinerja penyuluh dalam memberdayakan petani. Kinerja penyuluh pertanian dipersepsikan oleh tingkat kepuasan petani yang menerima jasa penyuluhan pertanian. Faktor-faktor yang berpengaruh positif dan nyata terhadap kinerja penyuluh pertanian dalam memberdayakan petani adalah: (1) Karakteristik petani (pendidikan, baik formal maupun non formal); (2) Karakteristik sistem sosial (nilai-nilai sosial budaya, akses petani terhadap lembaga penyuluhan dan fasilitas agribisnis oleh lembaga pemerintah terkait); dan (3) Kompetensi penyuluh pertanian (yaitu kompetensi penyuluh berkomunikasi; kompetensi penyuluh membelajarkan petani dan kompetensi penyuluh dalam interaksi sosial).